Current research on UV-induced DNA damage and its role in promoting the development of skin malignancies - ZHANG Boyuan; YAO Zhirong (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Skin malignancies include non-melanoma skin cancers and melanoma, with high incidence rates that pose a significant burden on public health and healthcare systems. Research in this area is crucial. Ultraviolet radiation (UV) is recognized as the primary risk factor for skin malignancies, with its main carcinogenic mechanism involving UV-induced DNA damage, which leads to the accumulation of mutations in key oncogenes and tumor suppressor genes. This accumulation promotes malignant transformation of related cells, ultimately resulting in the formation of malignant tumors. Understanding the specific processes through which UV-induced DNA damage contributes to the development of skin malignancies is crucial for advancing related research. Therefore, this paper focuses on the mechanisms of UV-induced DNA damage, the repair mechanisms for UV-induced DNA damage, and the relationship between UV-induced DNA damage and the occurrence of the three major types of skin malignancies.